THE SOCIAL-PHILOSOPHICAL ESSENCE OF MILITARY SERVICE AND ITS ROLE IN THE SPIRITUAL STABILITY OF SOCIETY - Muminov Fazliddin Qobil oglu, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  examines  the  socio-philosophical  essence  of  military service and its role in ensuring the spiritual stability of society. The study analyzes the ontological and axiological aspects of military service, highlighting its importance in transforming  individuals  from  personal  existence  to  social  responsibility.  It  also explores  the  relationship  between  military  service  and  concepts  such  as  duty, patriotism,  and  moral  consciousness.  Furthermore,  the  role  of  military  service  in shaping  ideological  immunity  in  the  context  of  modern  information  challenges  is substantiated.